DETERMINAN KONSERVATISME AKUNTANSI PERUSAHAAN: PERAN MODERASI FINANCIAL DISTRESS - Dayyanah, Malikhatun; Suryandari, Dhini (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2019)
The aim of this research is to examine the effect of leverage, interest conflict, and litigation risk on accounting conservatism with financial distress as the moderating variable. The population in this research is all manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the years 2015 to 2017 which consists of 155 companies. The sample selection used purposive sampling method, there are 30 companies as research sample and 90 units of analysis. Out of this amount, there are 21 units of analysis which are outlier data, so totally there are 69 units of analysis. Analysis of research data used are descriptive statistics and inferential statistics which are processed with IBM SPSS Statistics 23 software. The results show that leverage and litigation risk have significant positive effect on accounting conservatism. While interest conflict has no affection on accounting conservatism. Financial distress is able to moderate the influence of interest conflict on accounting conservatism, but it is not able to moderate the influence of leverage and risk of litigation on accounting conservatism.